Dampak Lingkungan Sekolah terhadap Prestasi Belajar Siswa: Analisis Studi Literatur - M. Sholehuddin Sulaiman; Anggraeni Lutfiyatul Afifah; Lely Ayu Munfaridah (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Abstract Purpose: Low learning outcomes are one of the frequently occurring problems. The school environment is one of the factors that affect learning outcomes. A comfortable, orderly, and attractive school environment, along with adequate facilities and infrastructure, can boost students' enthusiasm and lead to better learning outcomes. Design/methodology/approach: The research method used was a literature study that analyzed previous research on the relationship between the school environment and student academic performance. Research limitations/implications: The study is limited to secondary data analysis through literature review, which may restrict the scope of findings to previously published research. The implications suggest that educational institutions should prioritize environmental quality as a strategic approach to improve student academic performance. Findings: The research revealed that multiple environmental factors significantly impact student learning outcomes. A conducive physical environment, characterized by comfort, orderliness, and visual appeal, combined with adequate facilities and infrastructure, enhances student motivation and academic performance. Harmonious social interactions among school community members create a supportive learning atmosphere that positively influences educational achievement. Originality/value: This study contributes to the educational literature by providing a comprehensive synthesis of research on school environment-academic performance relationships